An Integrated Microfluidics Approach for Personalized Cancer Drug Sensitivity and Resistance Assay. Issue 11 (20th May 2019) - Desyatnik, Inna; Krasner, Matan; Frolov, Ludmila; Ronen, Maria; Guy, Ortal; Wasserman, Danit; Tzur, Amit; Avrahami, Dorit; Barbiro‐Michaely, Efrat; Gerber, Doron
Abstract: Cancer is the second leading cause of death globally. Matching proper treatment and dosage is crucial for a positive outcome. Any given drug may affect patients with similar tumors differently. Personalized medicine aims to address this issue. Unfortunately, most cancer samples cannot be expanded in culture, limiting conventional cell‐based testing. Herein, presented is a microfluidic device that combines a drug microarray with cell microscopy. The device can perform 512 experiments to test chemosensitivity and resistance to a drug array. MCF7 and 293T cells are cultured inside the device and their chemosensitivity and resistance to docetaxel, applied at various concentrations, are determined. Cell mortality is determined as a function of drug concentration and exposure time. It is found that both cell types form cluster morphology within the device, not evident in conventional tissue culture under similar conditions. Cells inside the clusters are less sensitive to drugs than dispersed cells. These findings support a heterogenous response of cancer cells to drugs. Then demonstrated is the principle of drug microarrays by testing cell response to four different drugs at four different concentrations. This approach may enable the personalization of treatment to the particular tumor and patient and may eventually improve final patient outcome. Abstract : Presented here is a microfluidic device that combines a drug microarray with cell microscopy. The device performs 512 experiments testing cellular chemosensitivity and resistance to a drug array. Different cell types form cluster morphology within the device, a phenomenon not evident in conventional tissue cultures. Cells inside the clusters are less sensitive to drugs than dispersed cells.